Pengaruh Penerapan CIRC Berbantuan Media Leaflet Terhadap Kemampuan Berpikir Kritis Siswa Materi IPAS SD: Penelitian - Nadia Selvira; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the effect of implementing the cooperative integrated reading and composition learning model assisted by leaflet media on the critical thinking skills of students of grade V science material at elementary school 17 Pontianak city. The method used was an experiment with a pre-experimental design with a one-group pretest-posttest design. The population of this study was all fifth-grade students at Elementary School 17, Pontianak City. The data collection technique used was a measurement technique and a written essay test was used as the data collection tool. Based on data analysis, the average pretest score was 42.50 and the average posttest score was 70.27. The results of the hypothesis test using a paired sample t-test showed a significant difference between the pretest and posttest scores with a significance value of 0.000, so ha was accepted. This proves that there is an effect of implementing a cooperative integrated reading and composition model assisted by leaflets on critical thinking skills. Based on the effect size calculation, it was obtained at 0.97, which is included in the large category. Thus, it can be concluded that the application of the cooperative integrated reading and composition model assisted by leaflet media has a positive influence on the critical thinking skills of fifth grade students at Elementary School 17 Pontianak City.